Differentiated Learning Strategy for Critical Thinking Skills in History Learning - Ramdhani, Rifa Shania (Proceeding International Conference on Religion, Science and Education, 2024)
Differentiated learning is a learning practice that began to be recognized with the implementation of the independent curriculum; differentiated learning is learning that adapts to the learning needs of each learner. Learning adaptation includes interests, learning styles and readiness to achieve learning goals, one of them is to increase the thinking process, namely critical thinking, which is the highest level of the thinking process. This research aims to see how differentiated learning can improve students' critical thinking. The research method is qualitative. The implementation of differentiated learning in learning history or social science focuses on the process that students do in their learning activities. Historical events teachers provide in the learning process need to be analyzed by students logically and structured to filter the information that students need to solve these learning problems. This ability is known as critical thinking. This differentiated learning influences students' critical thinking skills in learning history, a varied, differentiated learning process that facilitates students to think critically, expand their knowledge, and conclude and connect information obtained through small group discussions based on their learning style.